Forecasting models of bacterial leaf spot disease of mulberry for Birbhum district of West Bengal (The Journal of Plant Protection Sciences, 2020)
Bacterial leaf spot (BLS) caused by Xanthomonas campestris pv. mori was found to be one of the major foliar diseases in mulberry at farmers field in Birbhum district. BLS incidence appeared in May and continued up to November. The correlation coefficient between disease severity and meteorological parameters revealed that BLS disease severity showed significant positive correlation with max & min temperatures, min relative humidity, rainfall and number of rainy days. Step down multiple regression analysis revealed that the forecasting of BLS could best be done from min temp, minimum relative humidity and number of rainy days.
Keywords: meteorological factors; prediction; mulberry; Xanthomonas campestris pv. mori